Bioactive Bioflavonoids from Platonia insignis (Bacuri) Residues as Added Value Compounds - Ribeiro, Dayane C. [UNESP]; Russo, Helena M. [UNESP]; Fraige, Karina [UNESP]; Zeraik, Maria L.; Nogueira, Cláudio R.; da Silva, Patrícia B.; Codo, Ana C. [UNESP]; Calixto, Giovana M.F. [UNESP]; de Medeiros, Alexandra I. [UNESP]; Chorilli, Marlus [UNESP]; Bolzani, Vanderlan S. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
Platonia insignis fruit, popularly known as bacuri, is traditionally used in folk medicine for its anti-inflammatory and antioxidant properties. Therefore, this study determined the chemical composition and biological activities of the bacuri’s shell and seeds extracts, considered residues from its consumption and industrial uses. Four biflavonoids (GB-2a, GB-1a, morelloflavone, and volkensiflavone) were identified in the extracts by high-performance liquid chromatography-diode array detection (HPLC-DAD), liquid chromatography tandem mass spectrometry (LC-MS/MS), and liquid chromatography-solid phase extraction-nuclear magnetic resonance (LC-SPE-NMR) techniques. Morelloflavone was identified as the main compound in the shell ethyl acetate extract, being responsible for the high in vitro antioxidant (50% effective concentration (EC50) ranging from 8.0-10.5 µg mL−1 in different protocols), anti-glycant (80%), and moderate inhibition of nitric oxide (1.56 µg mL−1 for > 90% cell viability) activities. This extract showed promising in vivo anti-inflammatory activity evaluated through the paw edema protocol after its incorporation into a liquid-crystalline drug carrier system, reducing the edema by up to 31%. The results demonstrated the potential of the fruit for the development of drugs of natural origin and corroborated to add economic value to these discarded residues.
Keywords: Biflavanones; Bioactivities; Clusiaceae; Liquid-crystalline system; Platonia insignis